Characterization of failures in school buildings exposed in aggressive environment M4 of Falcón State (Gaceta Técnica, 2018)
The present investigation focused on establishing a characterization of public used reinforced concrete constructions such as school units in the coastal zone of Chichiriviche and Tucacas in Venezuela’s Falcon State, exposed to highly corrosive environments and built with inadequate construction techniques. The ultimate aim was to make recommendations to regional bodies so that they could make structural interventions more precisely and assertively. The study was carried out in seven educational units, in which planimetric surveys were carried out, the collection of fault symptoms, tests in some structural members and finally a general evaluation of damages that allowed identifying their durability and particular recommendations for each school building. As a result, these units of different construction ages were in a better state of conservation, when compared directly to the sample evaluated in 2006 in private multifamily buildings, which were even younger than this sample. It was recommended for all cases that they apply a programmed and technical continuous maintenance system, which goes beyond the systems of paints whose substrate is not properly prepared, resulting in a process of superficial repair and aesthetic ineffective.
Keywords: corrosion; durability of reinforced concrete